Untersuchungen zum Arbeitsfluss in getakteten Bauproduktionssystemen aus Perspektive von Generalunternehmern - Binninger, Marco (Karlsruher Reihe Technologie und Management im Baubetrieb, 2022)
A good workflow plays a crucial role in production in terms of productivity and efficiency. In construction, the use of tact creates flow.The scientific work takes on the flow and tact in construction. A workflow evaluation matrix for tacted construction projects is derived and 50 construction projects are examined with it. A theoretical potential for improvement of up to 80% in terms of workflow efficiency can be demonstrated. With the help of the derived improvement approaches including more.